Public relations and stakeholder participation models: organizations seeking consensus or conflict? - Paraventi, Ágatha (Organicom, 2017)
The text discusses the problems of participation between organizations and audiences for the decision-making process. It describes criticisms of models based on dialogue, on consensus (Grunig, 2002, 2009) and on deliberation by Habermas (Meisenbach, 2006, apud Davidson, 2016), which seek democratic decisions. The work provides contributions linked to the conflict, of the Parc model - politically responsible constructivist-relational theory (Deetz, 2009, 2010), and to dissent, of Mouffe’s agonistic democracy (Davidson, 2016). The empirical study links the Parc model to the practices of stakeholder engagement for sustainability in Brazilian organizations.